2015
DOI: 10.1016/j.tem.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular matrix and insulin resistance

Abstract: The extracellular matrix (ECM) is a highly dynamic compartment that undergoes remodeling as a result of injury and repair. Over the past decade, mounting evidence in humans and rodents suggest that ECM remodeling is associated with diet-induced insulin resistance in several metabolic tissues. Additionally, integrin receptors for the ECM have also been implicated in the regulation of insulin action. This review will address what is currently known about the ECM, integrins and insulin action in the muscle, liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
219
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(229 citation statements)
references
References 101 publications
(145 reference statements)
6
219
0
4
Order By: Relevance
“…Hypoxia constitutes an essential factor contributing to AT inflammation and fibrosis 17 . HIF-1α induction by AT hypoxia triggers the upregulation of genes involved in the fibrotic response, resulting in the excess deposition of ECM components, which may cause adipocyte death and inflammation, being also strongly associated with systemic insulin resistance 60,61 . In line with this observation, our data showed that genes involved in the regulation of hypoxic response (Hif1a), inflammation (Tnf, Emr1), and excessive collagen deposition (Col6a1 and Col6a3) were highly enriched in EWAT of leptin-deficient ob/ob mice.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia constitutes an essential factor contributing to AT inflammation and fibrosis 17 . HIF-1α induction by AT hypoxia triggers the upregulation of genes involved in the fibrotic response, resulting in the excess deposition of ECM components, which may cause adipocyte death and inflammation, being also strongly associated with systemic insulin resistance 60,61 . In line with this observation, our data showed that genes involved in the regulation of hypoxic response (Hif1a), inflammation (Tnf, Emr1), and excessive collagen deposition (Col6a1 and Col6a3) were highly enriched in EWAT of leptin-deficient ob/ob mice.…”
Section: Discussionmentioning
confidence: 99%
“…It is recently ascertained that fibrosis, excess deposition of ECM components, in metabolically active, insulin-sensitive tissues, including the skeletal muscle, adipose tissue and liver has damaging impact on glucose homoeostasis [6,120,121]. Obesogenic ECM remodelling of white adipose tissues is closely linked with the increased levels of circulating ECM proteins and ECM-derived peptides in parallel with increased levels of adipose-derived cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…pre-adipocytes, macrophages, and vascular endothelial cells, should contribute to adipose tissue inflammation, apoptosis, angiogenesis, and subsequent metabolic deteriorations in obesity. A similar concept has been proposed in the biology of the skeletal muscle and liver, which was recently reviewed elsewhere [6]. Despite a novel perception in the context of obesity and insulin resistance, ECM–ECM receptor pathways have been long implicated in the biology of pulmonary fibrosis, wound healing, and tumour growth [79].…”
Section: Introductionmentioning
confidence: 97%
“…These structural abnormalities likely also contribute to the increased apoptosis that we observed in insulin-resistant livers. The link between hepatic ECM and architectural structural remodeling with insulin resistance has been studied sparingly (Williams et al, 2015a). In one study, tail-vein injection of HFD-fed mice with a hydrolase for hyaluronan, an ECM component, reduces features of muscle and liver insulin resistance (Kang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%